Modelo CESM para gestionar la degradación y vida remanente en sistemas de transmisión de energía - Arias Velásquez, Ricardo Manuel (Pontificia Universidad Católica del Perú, 2021)
On the last twenty years, maintenance analysis and execution has changed, perhaps more than any other discipline in engineering. These changes are mainly based on the increase and variety of physical assets (industrial plants, equipment, buildings, among others). The designs are more complex, new methods of maintenance are applied and the optics in the organization has changed with respect to the maintenance and its responsibilities to assure the reliability of the system. Several developments have been presented to establish a model of greater coverage that allows the evaluation of the equipment. All the companies and goverments need a better reliability in their grid, and an asset management strategy for the remaining life management. However, the calculation of the probability of failure of an equipment is developed in this thesis, for power lines, transformers and circuit breakers. It can be determined by its state which is derived from the estimation of the remaining life. The remaining life recommended by international standards, does not consider the variety of conditions that present the national territory by geography, climate, among others. All equipment does not age at the same speed and is not subject to the same operating or environmental conditions. The knowledge contribution is an assessment model, for a better estimate of the reliability of the power system, with focus in remaining life for the asset and system, the case study has been done successfully, with power transformers, circuit breakers and cables of power lines with high accuracy and effectiveness. The research focused on the main elements of the power transmission system: Power transformer, switch and power lines, it‘s upper than 138 kV (High and very high voltage transmission system), for the physical assets associated to transmission system. In this thesis, the technical assessment for the reliability and remaining life analysis of the electric power system has been achieved, the results are the following: 8 objectives with 24 indicators for the 3 most important equipment of the power system: Inductive equipment, switchgear, cable and conductors of overhead lines. The model CESM developed, it includes the assessment of effectiveness of 98.13% in operating condition for power transformers, 99.36% for switches and 98.43% for overhead lines conductors. The benefits value with a costs analysis has identified savings of USD 22,606,831.60, it was obtained by applying the model. The results of improvement of costs and service level in the implementation of the model in Peru are presented, improving the indicators in switchgears, transformers and conductors of electric power transmission lines.
Keywords: Líneas eléctricas--Mantenimiento; Sistemas de energía eléctrica--Evaluación; Transmisión de energía eléctrica; https://purl.org/pe-repo/ocde/ford#2.07.03